2006
DOI: 10.1016/j.febslet.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of DC‐SIGN for mannose‐ and fucose‐containing glycans

Abstract: The dendritic cell specific C-type lectin dendritic cell specific ICAM-3 grabbing non-integrin (DC-SIGN) binds to ''self'' glycan ligands found on human cells and to ''foreign'' glycans of bacterial or parasitic pathogens. Here, we investigated the binding properties of DC-SIGN to a large array of potential ligands in a glycan array format. Our data indicate that DC-SIGN binds with K d < 2 lM to a neoglycoconjugate in which Galb1-4(Fuca1-3)GlcNAc (Le x ) trisaccharides are expressed multivalently. A lower sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(226 citation statements)
references
References 37 publications
13
206
0
7
Order By: Relevance
“…From a biological point of view, the most important characteristics of the FVIII/VWF complex is to show specificity for different carbohydrates and to show certain flexibility of the binding sites that would allow for the recognition of a range of structurally related carbohydrates as a regulation mechanism similar to that of other reported lectins (Vasta et al 1994;Hernández et al 2004). Vertebrate lectins fall into a number of structurally distinct families and participate in different intracellular functions, such as trafficking, sorting, and targeting of maturing glycoproteins, (Dodd and Drickamer 2001) as well as in extracellular functions, such as adhesive interactions (Zelensky and Gready 2005), by mediating interaction with the extracellular matrix or body fluids, or by mediating cell adhesion, cell signaling, inducing gene transcription, post-translational modifications, glycoprotein clearance, and pathogen recognition (Britten et al 1998;van Liempt et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…From a biological point of view, the most important characteristics of the FVIII/VWF complex is to show specificity for different carbohydrates and to show certain flexibility of the binding sites that would allow for the recognition of a range of structurally related carbohydrates as a regulation mechanism similar to that of other reported lectins (Vasta et al 1994;Hernández et al 2004). Vertebrate lectins fall into a number of structurally distinct families and participate in different intracellular functions, such as trafficking, sorting, and targeting of maturing glycoproteins, (Dodd and Drickamer 2001) as well as in extracellular functions, such as adhesive interactions (Zelensky and Gready 2005), by mediating interaction with the extracellular matrix or body fluids, or by mediating cell adhesion, cell signaling, inducing gene transcription, post-translational modifications, glycoprotein clearance, and pathogen recognition (Britten et al 1998;van Liempt et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DC-SIGN is also able to recognize branched fucosylated structures with terminal galactose residues, such as the Lewis antigens. This binding interaction on macrophages activates phagocytosis [48]. …”
Section: Dc-sign Inhibitors As Viral Anti-adhesivesmentioning
confidence: 99%
“…It should be noted that the mere presence of a potential CLR-binding ligand does not necessarily indicate binding-or functional activity, which should be experimentally established. For example, whereas high-mannose glycans are DC-SIGN ligands (77) and S. mansoni SEA contain high-mannose glycans, the major ligands for DC-SIGN on SEA are Le X and LDNF (71). For DC-SIGN elucidation of the crystal structure, in combination with studies on the interaction of the carbohydrate-recognition domain (CRD) with different glycan ligands, demonstrated that the structure of the glycan and its multivalency of presentation, as well as the docking of the glycan in the CRD(s) of the lectin, determine whether a high-affinity or high-avidity binding is established with a particular lectin (Fig.…”
Section: Can Helminth Compounds Suppress Inflammatory Responses Of DCmentioning
confidence: 99%